Mapping bureaucratic overload: Dynamics and drivers in media coverage across three European countries - Alexa Lenz; Yves Steinebach; Mattia Casula (Regulation & Governance, 2024)
Bureaucratic overburdening has emerged as an important theme in public policy and administration research. The concept signifies a state where public administrators are overwhelmed with more tasks and responsibilities than they can effectively handle. Researchers attribute this phenomenon to several key factors, such as an increasing assault on the public sector, a growing volume of policies to enforce, and “external” shocks. These studies converge on the perception that the public sector's capacity to effectively implement policies and to address societal problems is progressively diminishing. However, there is a clear knowledge gap regarding the breadth, dynamics, and pervasiveness of this issue, as existing research often narrows its focus on the implementation of specific policies or policy sectors. This paper addresses this research gap by mapping the frequency of bureaucratic overload reports in newspaper articles from Italy, Ireland, and Germany, spanning two decades from 2003 to 2022. In the second step, we describe the drivers of overload that we coded in a random sample of articles. Our research reveals that the overburdening of public administration is indeed an escalating problem resulting from an “explosive” cocktail of external and internal challenges that simultaneously affect public authorities.
Keywords: 330; administrative capacity; bureaucratic overload; external shocks; media; policy growth